WHO European Childhood Obesity Surveillance Initiative: Impact of Type of Clothing Worn during Anthropometric Measurements and Timing of the Survey on Weight and Body Mass Index Outcome Measures in 6–9-Year-Old Children. (27th April 2016) - Wijnhoven, Trudy M. A.; van Raaij, Joop M. A.; Spinelli, Angela; Yngve, Agneta; Lissner, Lauren; Spiroski, Igor; Farrugia Sant'Angelo, Victoria; Pérez-Farinós, Napoleón; Martos, Éva; Heinen, Mirjam; Kunešová, Marie; Rito, Ana I.; et al.
Abstract : Background . The World Health Organization European Childhood Obesity Surveillance Initiative (COSI) conducted examinations in 6–9-year-old children from 16 countries in the first two rounds of data collection. Allowing participating countries to adhere to their local legal requirements or adapt to other circumstances required developing a flexible protocol for anthropometric procedures. Objectives . (1) Review intercountry variation in types of clothing worn by children during weight and height measurements, clothes weight adjustments applied, timing of the survey, and duration of data collection; (2) assess the impact of the observed variation in these practices on the children's weight or body mass index (BMI) outcome measures. Results . The relative difference between countries' unadjusted and clothes-adjusted prevalence estimates for overweight was 0.3–11.5%; this figure was 1.4–33.3% for BMI-for-age Z -score values. Monthly fluctuations in mean BMI-for-age Z -score values did not show a systematic seasonal effect. The majority of the monthly BMI-for-age Z -score values did not differ statistically within a country; only 1–3 monthly values were statistically different within some countries. Conclusions . The findings of the present study suggest that the built-in flexibility in the COSI protocol concerning the data collection practices addressed in the paper can be kept and thus do not necessitate a revision of the COSI protocol.